THE ELECTRONIC STRUCTURE, STABILITY, THERMODYNAMICS AND VIBRATIONAL STUDY OF CIS ALKENYL SUBSTITUTED CHALCONES BY DENSITY FUNCTIONAL THEORY CALCULATIONS - HUSSEIN, HAVAL A. (Journal of Duhok University, 2023)
In this research, structural analysis and stability of six cis chalcone conformers were investigated, compared with trans conformers using the DFT-B3LYP method and basis set 6-311++G(d,p). Results obtained found that 1-Butenyl cis Chalcone (1-BC) possesses the greatest stability. The polarity of the solvent and the geometry of the conformer appeared to have a significant impact on the stability of the conformers. Additionally, cis 1-BC was appeared to cause the greatest shifts (7 cm-1-gas,6 cm-1-n-hexane and 6 cm-1-ethanol) in the magnitudes of vibrational frequencies of cis unsubstituted CA followed by cis divinyl chalcone (DVC) and cis   E-propenyl chalcone (E-PC). It is revealed that the 2-butenyl chalcone (2-BC) constitutes the highest values of Thermal-Energy (T-E), Entropy- (S) and Heat -Capacity (Cv).